Control of phase states in ring oscillators sharing inductors - Setou, Y.; Nishio, Y.; Ushida, A. (1997 IEEE International Symposium on Circuits and Systems, 2002)
In this study we show control of phase states in ring oscillators sharing inductors by infusing the voltage of the first oscillator into the other one. We confirm the suppression of the phase states of the original system and the generation of new phase states which we have not seen before infusing the voltage.